2022
DOI: 10.3390/vaccines10020282
|View full text |Cite
|
Sign up to set email alerts
|

What Drives the Value of a Shigella Vaccine?

Abstract: The development and licensure of a safe and highly efficacious Shigella vaccine has been a priority in international public health circles for decades and would represent a great scientific achievement. Nonetheless, in the context of increasingly crowded and costly childhood immunization programs, and with a myriad of other new and improved vaccines currently or soon on the market, there is no guarantee that even a highly effective Shigella vaccine would become a priority for adoption and introduction by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Currently, there is no vaccine against Shigella infection [ 16 , 17 , 40 ]. Based on the severity, disease burden, and emergence of antimicrobial resistance, Shigella has long been a priority for the WHO and other international organizations and the potential to prevent the disease in children would be a huge scientific breakthrough with substantial public health implications [ 17 , 18 ]. McQuade et al reported that when the latest technique (qPCR) was used compared to culture, there was an 11-fold increase in Shigella detection compared to previous reports [ 1 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is no vaccine against Shigella infection [ 16 , 17 , 40 ]. Based on the severity, disease burden, and emergence of antimicrobial resistance, Shigella has long been a priority for the WHO and other international organizations and the potential to prevent the disease in children would be a huge scientific breakthrough with substantial public health implications [ 17 , 18 ]. McQuade et al reported that when the latest technique (qPCR) was used compared to culture, there was an 11-fold increase in Shigella detection compared to previous reports [ 1 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the severity, disease burden, and emergence of antimicrobial resistance, Shigella has long been a priority for the WHO and other international organizations and the potential to prevent the disease in children would be a huge scientific breakthrough with substantial public health implications [ 17 , 18 ]. McQuade et al reported that when the latest technique (qPCR) was used compared to culture, there was an 11-fold increase in Shigella detection compared to previous reports [ 1 , 16 , 17 ]. In this study, it was reported that traditional culture methods may have missed the majority of Shigella cases; the lowest sensitivity was found in young children, who are the most vulnerable to adverse outcomes [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study add to the existing literature on vaccine assessments, value propositions, and investment cases [ 34 37 ], including a complementary paper reporting on national stakeholder findings regarding NGRVs [ 21 ]. Interviews with HPs on vaccine preferences elucidated potential barriers and facilitators for NGRV delivery, which align with previously published findings around vaccine feasibility and acceptability in LMIC settings [ 23 , 38 ].…”
Section: Discussionmentioning
confidence: 83%
“…Our findings also enhance the estimated value of Shigella vaccination, which is important as policy makers consider a multiplicity of other public health interventions. 35 These findings require assessment by large-scale vaccine trials in populations at high risk, ideally showing that non-acute health effects, such as linear growth faltering and stunting, even from less severe disease, can be ameliorated by vaccination .…”
Section: Discussionmentioning
confidence: 99%